The restructuring plan as competency instrument in the insolvent companies market - Águila Ruiz de Somocurcio, Paolo del (2015)
The restructuring plan is an instrument which, based on standards of efficiency and competence, allows insolvent companies to continue running in the market. Therefore, in order to turn a company in crisis into a competitive unit of business, comprehensive mechanisms may be established based on standards aimed by the market and consumers.This article addresses four essential aspects in order to understand the restructuring plan as a real instrument of competence in the market of insolvent companies: (i) its opposable nature; (ii) the treatment given to guarantees provided by the debtor; (iii) the consequences of the non observance of the plan; and (iv) the scope of this bankruptcy instrument according to IndecopI (Instituto Nacional de Defensa de la Competencia y de la Protección de la Propiedad Intelectual).